If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + y = x + -5 Reorder the terms: -1x + y = -5 + x Solving -1x + y = -5 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -1x + -1x + y = -5 + x + -1x Combine like terms: -1x + -1x = -2x -2x + y = -5 + x + -1x Combine like terms: x + -1x = 0 -2x + y = -5 + 0 -2x + y = -5 Add '-1y' to each side of the equation. -2x + y + -1y = -5 + -1y Combine like terms: y + -1y = 0 -2x + 0 = -5 + -1y -2x = -5 + -1y Divide each side by '-2'. x = 2.5 + 0.5y Simplifying x = 2.5 + 0.5y
| R+9.5=15.34 | | (c+d)2= | | 180n-360=162n | | 4y*4y=64 | | 4x-9=2+15 | | 9(x-2)+10x+10-20= | | 3=25x+6 | | 0=60x-16x^2 | | 5a+b+90=180 | | ln(3t)-ln(4t)=2 | | 4a-1=16.5 | | [3x+5]+4=13 | | 4=7m | | a(2a-1)(2a)=16.5 | | 80=-2(m+5)+m | | 8(1-8)=x+8 | | Cot^2(x)-cos(x)=1 | | 2a-1-a-2a=16.5 | | 180=5x-14+3x | | Cot^2x-cos(x)=1 | | 3(2x+10)-40+x+2x+10=162 | | (5+5i)(3-3i)=0 | | x^9=205 | | (100x^2-27)=0 | | -13=-22-3x | | 5a-1=16.5 | | 32-5[4+3(2+1)-6]= | | 9y-3=19-y | | y=50+2.5x | | 2x+10+x+3(2x+10)-40=162 | | 7+16x-1-4x=24+8x-9+3x | | X-6.4=-2.6 |